Dui weida daoshi Mao zhuxi xinhuai yige "zhong" zi, dui weida Mao Zedong sixiang hen zhua yige "yong" zi
'With regard to the great teacher Chairman Mao, cherish the word "loyalty". With regard to the great Mao Zedong Thought, vigorously stress the word "usefullness"'. Printno. T8081.10394.